2015
DOI: 10.1016/j.cogdev.2014.12.008
|View full text |Cite
|
Sign up to set email alerts
|

Imagination and the generation of new ideas

Abstract: a b s t r a c tA variety of theories have been put forth to explain the function of imagination, most notably that imagination engages and develops children's theory of mind and counterfactual reasoning. Here, we propose that a primary role for imagination is as a cognitive mechanism for efficiently generating new ideas without observing new evidence. Learners must generate hypotheses before they can assess the truth of these hypotheses. Given infinite possibilities, how do learners constrain the process of hy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 25 publications
(31 reference statements)
0
21
0
1
Order By: Relevance
“…In addition, both preschoolers and adults privilege efficient design (selecting an object with a single feature for a single purpose over one with superfluous features; Kelemen, Seston, & Saint Georges, 2012), and map the quantity and diversity of object functions to infer the complexity of its internal mechanism (Ahl & Keil, 2016). Preschoolers also map the type of effect produced (i.e., discrete vs. continuous) to the mechanism that produced it (a binary "on/off" switch vs. a dial), providing evidence that even children relate the physical structure of an object's mechanism to its effect (Magid, Sheskin, & Schulz, 2015).…”
Section: Design Facilitates Discoverymentioning
confidence: 99%
“…In addition, both preschoolers and adults privilege efficient design (selecting an object with a single feature for a single purpose over one with superfluous features; Kelemen, Seston, & Saint Georges, 2012), and map the quantity and diversity of object functions to infer the complexity of its internal mechanism (Ahl & Keil, 2016). Preschoolers also map the type of effect produced (i.e., discrete vs. continuous) to the mechanism that produced it (a binary "on/off" switch vs. a dial), providing evidence that even children relate the physical structure of an object's mechanism to its effect (Magid, Sheskin, & Schulz, 2015).…”
Section: Design Facilitates Discoverymentioning
confidence: 99%
“…can be invalidated a priori, even without knowing the correct answer. In recent experiments, Tsividis et al (2015) found that children can use high-level abstract features of a domain to guide hypothesis selection, by reasoning about distributional properties like the ratio of seeds to flowers, and dynamical properties like periodic or monotonic relationships between causes and effects (see also Magid et al 2015).…”
Section: Thinking Fastmentioning
confidence: 99%
“…This idea can lead us to a second interpretation of the present results; namely, to goal orientation. In other words, at older ages children have already started to understand that certain problems require solutions with specific characteristics (Magid, Sheskin, & Schulz, 2015). This could show that children start grasping the idea of goals and searching for answers that fit the characteristics of the problem; this is shown by the 6-7 years old children in Study 1, who either solved the problem with the target object or with one that resembled the characteristics of the target object.…”
Section: Insight Problem Solving With Known and New Objectsmentioning
confidence: 99%
“…Our second study showed that, as compared to adults, children gave more unusual answers for new objects. This finding may be closely related to imagination, which provides the individual with the chance to infer a richer set of links between the elements of the situation/object/problem (Magid et al, 2015).…”
Section: Insight Problem Solving With Known and New Objectsmentioning
confidence: 99%
See 1 more Smart Citation